Effects of Stem Cells and Granulocyte Colony Stimulating Factor in Reperfusion Injury (Iranian Journal of Kidney Diseases, 2010)
Introduction. Bone marrow-derived stem cells have a potential capacity to differentiate and accelerate recovery in injured sites of body. Also, factors like granulocyte colony stimulating factor (GCSF) can promote their mobilization to the injured sites. We aimed to investigate the role of GCSF as an alternative therapeutic option instead of mesenchymal stem cells (MSCs) in reperfusion injury.Materials and Methods. Twenty-nine rats with induced reperfusion injury were divided into 3 groups to receive MSC, GCSF, or nothing (control). Kidney function was assessed by blood urea nitrogen and serum creatinine levels. Histological grading was performed to evaluate the extent of tubular injury and the rate of recovery.Results. All the rats reached recovery after 14 days. Rats in the MSC group reached early functional and histological recovery compared to the controls on the 7th day of the study (P = .01 and P = .02, respectively). Compared to the control group, the GCSF group showed a more significant histological recovery on the 7th day (P = .04), but kidney function was ameliorated on the 14th day (P = .04). Both the GCSF and control groups had a significant number of CD34+ cells, which were detected by flow cytometry on the 7th day after reperfusion injury.Conclusions We found therapeutic effects following administration of both MSC and GCSF which was more evident with MSC in the setting of reperfusion injury. More investigation is required to find optimal time, dose, and route of administration as well as other possible contributing factors.